Spinal Sagittal Alignment, Hospital Anxiety and Depression Scale Scores, and Patient-Reported Outcome among People with Sporting Activity - Shin Oe; Yu Yamato; Tomohiko Hasegawa; Go Yoshida; Sho Kobayashi; Tatsuya Yasuda; Tomohiro Banno; Hideyuki Arima; Yuki Mihara; Hiroki Ushirozako; Tomohiro Yamada; Koichiro Ide; et al. (Asian Spine Journal, 2020)
Study Design Retrospective cohort study. Purpose This study aimed to investigate how participation in sporting activity affects patient-reported outcome (PRO), including Neck Disability Index (NDI), in males and females. Overview of Literature Previously, our study reported that factors with a negative influence on the NDI in females were a lack of sporting activities. However, it was still unclear why it affected poor scores of NDI. Methods The subjects were 473 volunteers. They were divided into two groups (activity and non-activity) according to participation or non-participation in sporting activities using a self-filled questionnaire. The evaluation items were height, weight, grip strength, bone density, Hospital Anxiety and Depression Scale (HADS) score, standing radiographic parameters, PRO (evaluated by EuroQol-5 dimension [EQ-5D], Oswestry Disability Index [ODI]), and NDI. Results There were 101 males in the non-activity group and 69 in the activity group and 178 females in the non-activity group and 125 in the activity group. For the males, the evaluation items with significant influence were cervical lordosis (non-activity group:activity group, 17°:22°) and T1 slope minus cervical lordosis (10°:6°, p<0.05). For the females, the evaluation items with significant influence were sagittal vertical axis (28:14 mm), HADS (10.4:8.4), EQ-5D (0.79:0.86), ODI (17:12), and NDI (12:9, p<0.01). HADS and PRO in the females were significantly correlated with the EQ-5D (−0.40), ODI (0.43), and NDI (0.55). Conclusions Males who participated in sporting activities had better cervical spine alignment but no effect on PRO. Females with sporting activities had better spinal global alignment and less mental stress. It is suggested that sporting activity in females might be associated with PRO because HADS highly correlates with PRO.